ANALYSIS OF CONNOTATION AND DENOTATION MEANINGS IN DAILY CONVERSATIONS OF TEENAGERS IN BAMBOO VILLAGE, SUB-DISTRICTUNA-UNA, TOJO UNA-UNA DISTRICT - Siti Hadija Alaydrus (Journal of Linguistica, 2024)
This study explores the connotation and denotation meanings in adolescent conversations in Bamboo Village, Una-Una District, emphasizing the importance of understanding words to prevent miscommunication. Employing a qualitative descriptive method and a semantic approach, the research uses primary data collected directly through observation, listening, recording, and documentation. Data analysis involves reduction, presentation, and verification of oral conversations recorded in two settings: Bamboo Village's port and a residential yard. The findings reveal that teenagers frequently use connotative terms such as "shoot" (expressing love), "stone head" (stubborn), and "eat heart" (disappointment). Denotative meanings appear in phrases like "a lot of fleas," "like to eat mangoes," and "fight." The study highlights the importance of distinguishing between literal and figurative meanings, enabling adolescents to communicate more effectively, express themselves accurately, and avoid misunderstandings. The research contributes to semantic studies by underscoring the role of connotative and denotative awareness in social interactions, helping adolescents select appropriate words, foster better relationships, and articulate their identities and values. The study encourages further exploration of connotations and denotations in diverse social contexts, aiming to deepen insights into language use in varying situations